THE EFFECT OF WARM WATER FOOT SOAKING THERAPY ON THE REDUCTION OF BLOOD PRESSURE IN ELDERLY HYPERTENSION PATIENTS IN WORKING AREA PUSKESMAS KOLSER KECAMATAN KEI KECIL MALUKU TENGGARA - Asyik, Kamaludin; Puspita, Sylvie; Rustanti, Elly (LPPM STIKES HUSADA JOMBANG, 2020)
Hypertension in the elderlyis caused by changes in the elasticity of the aortic wall decreases, The hear valve thickens and becomes rigid, the heart’s ability to pump blood decreasesby one persent (1)% every year after twenty years of age, the ability of the heart to pump out decreases causing decreased contraction and volume. Besides losing the elasticity of bloodvessels. Research objectives determine the effect of warm water foot bath to decrease blood pressure in elderly hypertensive in Working Area Puskesmas Kolser kecamatan Kei Kecil Maluku Tenggara. This research was conducted using designthis research was conducted using design quasi experiment design pretest and posttest nonequivalent control group, data retrieval technique using saturated sampling were 38 respondents elderly hypertension. Data were collected using observation sheets and spigmomanometer to determine the effect of warm water foot bath. Analysis of studies using paired t-test and independent t test with a level signifiksi α < 0,05. The results showed no significant differences in systolic and diastolic blood pressure before and after the warm water foot bath (p value 0,000 dan p value 0,000). Foot soak using warm water is expected to be an alternative treatment, because it is easily available, cheap and practical.